The 5 choices : the path to extraordinary productivity - Kogon, Kory; Merrill, Adam; Rinne, Leena (Simon & Schuster, 2015)
"Franklin Covey offers powerful insights drawn from the latest neuroscience and decades of experience and research in the time-management field to help you master your attention and energy management through five fundamental choices that will increase your ability to achieve what matters most to you. The 5 Choices is time management redefined for the twenty-first century: it increases the productivity of individuals, teams, and organizations and empowers you to make more selective, high-impact choices about where to invest your valuable time, attention, and energy"--Publisher's website.